On the impact failure behavior of triaxially braided composites subjected to metallic plate projectile. (1st April 2020) - Zhao, Zhenqiang; Dang, Haoyuan; Liu, Peng; Guo, Zaoyang; Zhang, Chao; Li, Yulong
Abstract: Experimental and numerical studies are conducted to study the impact failure behavior of a typical 0°/±60° two-dimensional triaxially braided composite (2DTBC). A single-stage gas gun test system is employed to perform the high-speed impact tests, where high-speed cameras and three-dimensional (3D) digital image correlation (DIC) technology are used to monitor the deformation and failure process of the target panels as well as the impact conditions of a plate-like projectile used to simulate a broken turbine blade. The impact resistance of the 2DTBC panel is experimentally analyzed based on the failure morphologies detected using an optical microscope and the internal damage distribution as measured by X-ray computed tomography (CT) scans. A multi-scale finite element model is used to model and predict the impact failure behavior of 2DTBC panels under different impact conditions. A comparison between numerical simulation results and experimental results validates the feasibility and accuracy of the proposed model and demonstrates the excellent crack propagation resistance of the 2DTBC. Numerical parametric studies were performed to examine the influence of the projectile deflection angle on the impact failure.